2016
DOI: 10.1002/jso.24488
|View full text |Cite
|
Sign up to set email alerts
|

Gender as a risk factor for adverse intraoperative and postoperative outcomes of elective pancreatectomy

Abstract: Male gender is a significant predictor of increased operative time, length of stay, transfusions, EBL > 1L, as well as postoperative organ space surgical site infections in these patients. J. Surg. Oncol. 2017;115:131-136. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 20 publications
5
27
2
Order By: Relevance
“…Men have more intra-abdominal visceral adipose tissue than women [39]. Similar to our study, a past investigation found that male sex was a significant predictor of increased operative time, length of stay, transfusions, blood loss, and postoperative surgical-site infections [9]. Male sex is a risk factor for morbidity after LDP owing to the increased likelihood of visceral obesity and the technical difficulty associated with operating on patients with visceral obesity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Men have more intra-abdominal visceral adipose tissue than women [39]. Similar to our study, a past investigation found that male sex was a significant predictor of increased operative time, length of stay, transfusions, blood loss, and postoperative surgical-site infections [9]. Male sex is a risk factor for morbidity after LDP owing to the increased likelihood of visceral obesity and the technical difficulty associated with operating on patients with visceral obesity.…”
Section: Discussionsupporting
confidence: 86%
“…We performed multivariate analyses using the candidate variables that were introduced as risk factors for complications after distal pancreatectomy in previous studies, as discussed below [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, our previous studies and along with others have supported that overweight body status (body mass index greater than or equal to 25 kg/m 2 ) contributes to adverse perioperative outcomes for pancreatectomies . Overweight body status is associated with increased operation duration, blood loss, and superficial SSI . Our report emphasizes the increasing risk for readmission with overweight individuals.…”
Section: Discussionsupporting
confidence: 73%
“…24,;25 Overweight body status is associated with increased operation duration, blood loss, and superficial SSI. [24][25][26] Our report emphasizes the increasing risk for readmission with overweight individuals. Although ERAS pathways have been shown to decrease length of stay without compromising outcomes, BMI may be an important variable in risk stratification for choosing patients to participate in ERAS pathways.…”
Section: Discussionmentioning
confidence: 63%
“…Sex is a factor, which plays an important role when estimating the probability of disease and complication across all fields of medicine. With regard to SSI, previous studies have demonstrated that generally, SSI occur more frequently in men than in women [35]. However, when looking at specific procedure types, this statement is not always accurate.…”
Section: Introductionmentioning
confidence: 99%